Les aspects satiriques, l’identité, la déviance et les structures de pouvoir dans le roman Balzac et la Petite Tailleuse chinoise - Seyidova, Leyla; Yegani, Marc M. (My University, 2018)
Dai Sijie's novel takes place during the Chinese Cultural Revolution and Balzac and the Chinese Little Tailor indirectly criticizes the communist regime, but in a satirical way. The books of the novel play a central role in the creation and preservation of the personal identities of the characters by means of acts of deviance. They also have a great role in establishing power structures between characters.
Satirical aspects, identity, deviance and power structures in the Balzac novel and the Chinese Little Tailor
Presented on April 23, 2018 at Student Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: Balzac and the Chinese Little Tailor; Dai Sijie; literary criticism